A comparative study of TCP and UDP performance using NS-3 simulation - Guo, Gaoyang; Cui, Zhiyi; Faizan Qamar; Azana Hafizah Mohd Aman (Penerbit Universiti Kebangsaan Malaysia, 2025)
As the center of the protocol layer, the transport layer is independent of the current network and transports data from the source device to the target device reliably and efficiently. Transmission Control Protocol (TCP) is a component of the transport layer that uses Internet Protocol (IP) protocol to achieve end-to-end data transmission. This paper investigates the experimental evaluation of TCP performance in recent years. Most of the studies get the performance results of TCP by comparing it with User Datagram Protocol (UDP). Therefore, in the simulation test conducted in this paper, the performance of TCP is judged by the performance comparison method of TCP and UDP. In this simulation, the NS-3 simulator was selected to complete the simulation. Choose throughput, end-to-end delay, lost packets, packet loss ratio, bandwidth utilization, jitter, and packet delivery ratio to perform numerical calculations. Then compare and summarize these performance metrics. Experimental results show that TCP has good performance, but its performance is affected by bandwidth, network delay, and other factors. Finally, the experimental results are organized and discussed, then plan the future work.